2005
DOI: 10.2214/ajr.184.5.01841624
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-31 MR Spectroscopy in Pediatric Liver Transplant Recipients: A Noninvasive Assessment of Graft Status with Correlation with Liver Function Tests and Liver Biopsy

Abstract: Phosphorus-31 MR spectroscopy is a feasible technique for the noninvasive assessment of host-related complications in pediatric patients after liver transplantation. Our preliminary data suggest that the technique may be integrated with MRI for the investigation of impaired liver function in transplant recipients when neither a biliary complication nor a vascular complication is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…1.5 [47] Effects of intravenous ATP infusion for 22-24 hours on liver energy status in advanced lung cancer patients.…”
Section: [43]mentioning
confidence: 99%
“…1.5 [47] Effects of intravenous ATP infusion for 22-24 hours on liver energy status in advanced lung cancer patients.…”
Section: [43]mentioning
confidence: 99%
“…Studies utilizing this method have shown promise in differentiating the etiology of diffuse parenchymal disease [56][57][58] as well as liver regeneration subsequent to resection 59 and transplant complications not related to vascular or biliary etiology. 60 …”
Section: Mr Spectroscopymentioning
confidence: 99%
“…Both 31 P MRS and 1 H-MRS have been applied to estimate liver lipid content. In vivo hepatic 31 P MRS provides non-invasive information about phospholipid metabolism, intrahepatocellular lipids and also hepatic functional status [90][91][92]. A typical 31 P MRS spectrum of the human liver in vivo contains resonances which can be assigned to phosphomonoesters, phosphodiesters, inorganic phosphate, and nucleotide triphosphates, including ATP [90].…”
Section: Magnetic Resonance Spectroscopy Study Of Nonadipose Tissues mentioning
confidence: 99%